Toleransi Beragama Di Sekolah - M. Wahid Nur Tualeka (Universitas Muhammadiyah Surabaya, 2019)
AbstractThe formulation of the problems that existed in this study were: a) What was meant by education tolerance? b) What efforts had been made by the school to develop tolerance education in SDN Bulak Banteng II/572 Surabaya? c) What was the effect of tolerance education on student's character? The purpose of this study was: 1) to understand what was meant by tolerance education, 2) to examine school efforts in developing tolerance education in SDN Bulak Banteng II/572 Surabaya, 3) to describe the effect of tolerance education on student's character.This thesis used a type of qualitative research. The sources of data obtained from primary data i.e. the results of interviews as the field research, questions and answers to teachers, employees, and some students of SDN Bulak Banteng II/572 Surabaya. The secondary data (supporting data) i.e. from the literature relating to the subject matter of research. The methods of data collection were from interviews, observation, and documentation. While the data analysis used a descriptive method of phenomenological analysis which aimed to describe the existing phenomenon of tolerance between religious people in SDN Bulak Banteng II/572 Surabaya. Keywords: Implementation, Religion Tolerance.